PECULIARITIES OF TRANSLATION POETRY TEXTS IN ENGLISH - BOBOEV LOIQ SAMIEVICH (JETA (Journal of English Teaching and Applied Linguistic), 2023)
This article deals with the problems in translating literary poesy and reveals some pertinent solutions and also concentrates on the need to expand the perimeters of Translation Studies. Unfortunately, the translators lay more emphasis on the translation of poetry; there should be more research regarding the particular problems of translating literary poetry. One explanation of this could be the fact that the status of poetry is considered higher, but it is more possibly due to the notable flawed notion that the novels, essays, fiction etc. possess a simple structure compared to that of a poem and is thus easier to translate. However, many debates have been organized over when to translate, when to apply the close local equivalent, when to invent a new word by translating clearly, and when to copy.